A problem of limited-access special lanes. Part I: Spatiotemporal studies of real freeway traffic. (October 2015) - Cassidy, Michael J.; Kim, Kwangho; Ni, Wei; Gu, Weihua
Highlights: Freeways with limited-access special lanes (e.g. carpool lanes) are examined. Spatiotemporal analysis of traffic data shows that access points can be bottlenecks. The bottlenecks can severely degrade flows and speeds in all freeway lanes. Abstract: Most special-use freeway lanes in the US, whether reserved for carpools, toll-paying commuters or both, are physically separated from the adjacent regular-use lanes by some form of barrier. Vehicle movements in and out of a special lane of this type are permitted only at select access points along the route. The barrier at each select point might open for a distance of 400 m or so. Limiting access in this way is said to reduce the "turbulence" that might otherwise occur were the special lane not to have a barrier, such that vehicles could instead enter or exit that lane anywhere along its length. Yet, real freeway traffic studied in spatiotemporal fashion shows that access points are prone to become bottlenecks. The problem occurs when traffic in the regular lanes becomes dense, as commonly happens during a rush. Drivers then seek refuge in the special lane in greater numbers. Since the vehicular maneuvers through the access point are focused within a limited physical space, they can become disruptive and further degrade traffic. Degradation can occur both in the special lane and in the adjacent regular ones. The damage can be worse than when there is no barrier to limit special-lane ingress and egress. The problem is shown to be reproducible across sites and across days at each site. Policy implications are discussed. Select designs and policies to address the problem are thereafter explored in Part II of the paper using traffic simulation.